Pengembangan Sistem Absensi Karyawan di Institut Informatika dan Bisnis Darmajaya Dengan Menggunakan Teknologi Barcode - Bagus Yuda Pratama; Fauziah Zahra Ramadhani; Munaa Munaa; Muhammad Said Hasibuan (Puslitbang Akademi Relawan TIK Indonesia, 2023)
There are so many ways to process employee attendance, one of which is to use the manual method. So far, there are still many large companies that still implement attendance manually, but this causes a lot of time leaks or other violations, which of course makes it less effective and efficient and causes attendance information to be inaccurate. In a company with quite a lot of employees, it is very necessary to have proper, fast, accurate attendance management. An accurate methodology for solving problems in this modern era with the use of QR barcodes because it will really help companies to attend to employees in real time. The system is made with the PHP programming language and uses the MYSQL database. The purpose of QR Code (Quick Response Code) technology in companies is as a tool in processing employee attendance data, employee identity cards and also processing employee data which is beneficial for employees because they can carry out computerized attendance activities. The results to be obtained from the research and implementation of this system are by entering several examples of employee data as an experimental form of attendance transactions, and the attendance application program is made to run properly. The system created produces several features in the form of user features, checking QR codes for attendance, generating QR codes from each employee card, recapitulation and attendance reports on the system, and employee data in the form of employee names, positions, work shifts and work location placements